The association between trauma and paediatric trigger thumb deformity; experience from a single tertiary referral hospital. Issue 1 (28th February 2023) - Salloum, Nadia L.; McGee, Pauline; Lam, Wee L.
Abstract: Whilst the natural history and management of trigger thumb have been thoroughly investigated, the aetiology of the condition remains poorly understood. There are suggestions that this could be a congenital or acquired condition, but evidence remains limited. A history of trauma has repeatedly been noted in a proportion of patients presenting with trigger thumb. This retrospective study reviewed the presentations of 75 cases of trigger thumb in 65 consecutive children who underwent surgery for trigger thumb. We found that 28% of affected digits presented with a traumatic history to the thumb, of those 90% presented immediately post-injury with a flexion deformity. Those who presented with a traumatic history were typically younger at presentation (median age 27.0 months compared to 37.5 months for traumatic and atraumatic presentations respectively) but also tended to present earlier than the atraumatic group (one day compared to 12.17 months respectively). We conclude that a single traumatic event is unlikely to be the causative factor in the development of trigger thumb in children but it may expediate the development of individuals who are predisposed.